Analysis of Magnetic Anisotropy and the Role of Magnetic Dilution in Triggering Single‐Molecule Magnet (SMM) Behavior in a Family of CoIIYIII Dinuclear Complexes with Easy‐Plane Anisotropy. Issue 48 (27th July 2017) - Palacios, María A.; Nehrkorn, Joscha; Suturina, Elizaveta A.; Ruiz, Eliseo; Gómez‐Coca, Silvia; Holldack, Karsten; Schnegg, Alexander; Krzystek, Jurek; Moreno, José M.; Colacio, Enrique
Abstract: Three new closely related Co II Y III complexes of general formula [Co(μ‐L)(μ‐X)Y(NO3 )2 ] (X − =NO3 − 1, benzoate2, or 9‐anthracenecarboxylato3 ) have been prepared with the compartmental ligand N, N ′, N ′′‐trimethyl‐ N, N ′′‐bis(2‐hydroxy‐3‐methoxy‐5‐methylbenzyl)diethylenetriamine (H2 L). In these complexes, Co II and Y III are triply bridged by two phenoxide groups belonging to the di‐deprotonated ligand (L 2− ) and one ancillary anion X − . The change of the ancillary bridging group connecting Co II and Y III ions induces small differences in the trigonally distorted CoN3 O3 coordination sphere with a concomitant tuning of the magnetic anisotropy and intermolecular interactions. Direct current magnetic, high‐frequency and ‐field EPR (HFEPR), frequency domain Fourier transform THz electron paramagnetic resonance (FD‐FT THz‐EPR) measurements, and ab initio theoretical calculations demonstrate that Co II ions in compounds 1 –3 have large and positive D values (≈50 cm −1 ), which decrease with increasing the distortion of the pseudo‐octahedral Co II coordination sphere. Dynamic ac magnetic susceptibility measurements indicate that compound 1 exhibits field‐induced single‐molecule magnet (SMM) behavior, whereas compounds 2 and3 only display this behavior when they are magnetically diluted with diamagnetic Zn II (Zn/Co=10:1). In view of this, it is always advisable to use magnetically diluted complexes, in which intermolecular interactions and quantum tunneling of magnetism (QTM) would be at least partly suppressed, so that "hidden single‐ion magnet (SIM)" behavior could emerge. Field‐ and temperature‐dependence of the relaxation times indicate the prevalence of the Raman process in all these complexes above approximately 3 K. Abstract : CoY magnetic complexes : Three Co II Y III dinuclear complexes that only differ in the ancillary bridging ligand connecting the Co II and Y III ions (nitrato, benzoato, or 9‐anthreacenecarboxylato) are reported. These complexes exhibit field‐induced single‐molecule magnet (SMM) behavior either in their bulk or magnetic diluted versions.